Numerical study of pile behaviour adjacent to braced excavation in clay - Delin, Jonathan Louis (Nanyang Technological University, 2021)
Piles are often subjected to lateral loads induced by geotechnical activities such as tunnelling, embankment, and excavation. These lateral loads could be detrimental to piles should it induce excessive lateral soil deformation. This report will specifically focus on pile behaviour with respect to adjacent deep excavation and exploration of methods to minimise pile response. In the first part of the project, parametric studies utilising plane strain finite element analyses are conducted to examine and quantify the effects of wall stiffness (flexible sheet pile wall and diaphragm wall), soil stiffness (Eu/Cu = 300, Eu/Cu = 200, and Eu/cu = 100), pile distance from retaining wall (3m, 6m, 9m, 12m, and 15m), pile diameter (0.6m, 0.8m, 1.0m, and 1.2m), and pile head fixity (free and pinned). These numerical analyses will be conducted using the PLAXIS 2D software. Comparisons between the effects of these parameters are presented in the report. In the second part of the project, finite element analyses are conducted to explore methods to reduce pile response. The methods studied are placement of concrete partition wall between the pile and excavation, installation of jet grout wall between pile and retaining wall, and jet grouting below the base of the excavation. The depth at which the partition and jet grout wall is installed will also be varied (15m, 25m, and 33m). The Comparison would also be conducted on the influence of these methods on the pile response. This study will focus on the lateral deflection and bending moment of pile induced by the adjacent deep excavation. The results from the first part of the project indicate the increase in pile deflection and bending moment with the use of a more flexible wall. However, a pile with larger diameter result in smaller deflection but larger bending moment. Furthermore, a flexible wall would increase pile deflection and bending moment for all types of piles. However, when the effects of wall stiffness and soil stiffness are compared for piles of different sizes and distance from wall, different trends in incremental lateral displacement and bending moment are observed. Additionally, the results from the second part shows the contribution of the 33m partition wall and jet grout wall to the reduction in pile deflection and bending moment. Moreover, in the case of jet grout installed below the base of the excavation, the pile exhibits large reduction in deflection and bending moment. These results suggests that these methods show promise to be used in the field to minimise pile response induced by deep excavation.